Sistem Rekrutmen Online Berbasis TOPSIS untuk Seleksi Kandidat - Faturrohman, Adit; Sulianta, Feri (Institut Teknologi Garut, 2025)
An efficient and accurate recruitment process is crucial for companies to ensure the quality of human resources that support growth and innovation. For Coffee Kane, acquiring the best talent is key to maintaining competitive advantage. However, traditional recruitment methods often face challenges, such as time inefficiency, high operational costs, and limitations in the search for quality candidates. This study proposes a web-based online recruitment system that integrates the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method. This system is designed to accelerate the selection process, reduce operational costs, and expand the search for candidates without geographical limitations. The implementation of this system has successfully automated the selection process, increased efficiency, and resulted in more accurate, objective, and transparent decision-making in selecting the best candidates.